Prikrita delovna razmerja - Kresal, Barbara (Delavci in delodajalci, 2014)
The contribution analyses the problem of disguised employment relationships which means that a person performs work for another on the basis of a false status of a self-employed person and/or on the basis of different civil law contracts, although - taking into account all circumstances - a person actually performs work for another in a dependent employment relationship. All persons performing work for another in a dependent relationship which has the elements of an employment relationship should be treated as employees. That means that all rights, guaranteed by employment legislation, should be recognized to them as well. Effective supervision by the labour inspection and accessible judicial protection as well as clear criteria for the assessment of existence of the elements of an employment relationship are the necessary precondition for achieving better compliance with the labour law rules in this regard in practice.
Keywords: delovna razmerja; delovno pravo; kršenje; pogodba o zaposlitvi